Диспергування емульсій у багатоступеневих кавітаційних апаратах - Литвиненко, Олександр Анатолійович; Пащенко, Богдан Сергійович; Кадомський, Сергій Віталійович (My University, 2018)
У статті представлено експериментальні результати обробки емульсій у гідродинамічних кавітаційних апаратах. Встановлено, що використання багатоступеневих апаратів сприяє спрощенню технологічної схеми і забезпечує необхідну якість готового продукту. Отримані результати дають підставу зробити висновки, що вибір багатоступінчастої обробки обумовлений необхід ністю відмови від циркуляційної схеми. Реалізація циркуляційної обробки призводить до погіршення якості кінцевого продукту. З’ясовано, що використання одноступінчатих кавітаційних апаратів для обробки емульсій неефективне, оскільки отриманий продукт не відповідає необхідним параметрам. Робочі режими відповідають бульбашковій формі кавітації, коли колапс кавітаційних буль башок супроводжується «жорсткою» ударно-хвильовою дією на компоненти середовища. Порівняльний аналіз одержаних результатів дає підстави ствер джувати, що при обробленні в одноступеневому апараті емульсія не досягає високих показників дисперсності. Використання апаратів з послідовними зонами кавітаційної обробки дає змогу одержувати емульсію з потрібними дисперсійними характеристиками.

The article presents the experimental results of the processing of emulsions in hydrodynamic cavitation apparatus. It has been established that the use of multistage apparatus contributes to the simplification of the technological scheme and ensures the required quality of the finished product. The authors have designed and manufactured an experimental setup for research. The results obtained give grounds to conclude that the choice of multi-stage processing is due to the need to abandon the circulation scheme. The implementation of the circulation treatment leads to a deterioration in the quality of the final product. It is established that the using of single-stage cavitation apparatus for processing emulsions is inefficient, because the resulting product does not match the required characteristics. When the collapse of cavitation bubbles is accompanied "hard" shock-wave action on the components of the environment than the operating modes correspond to bubble form of cavitation. Comparative analysis of the results allows arguing that emulsion does not achieve high dispersion when processing in a single stage apparatus. The content of coarse disperse particles is significantly reduced at the two-stage processing, which indicates about the intensification of shock-wave action on the emulsified component of collapsing cavitation bubbles. This indicates a significant increase the content in the emulsion of the small disperse component. The using of devices with succe ssive zones of cavitation treatment allows to obtaining an emulsion with the necessary dispersion parameters. The use of two stage apparatus improves the quality of emulsions. However, a three-stage treatment in HDC with a value of Re 11.6—8.2 allows to obtaining a finely dispersed emulsion with an oil phase size of 3.5—4.6 mkm. It was found that with increasing Re dispersion decreases, and the emulsion acquires an increased delamination resistance. On the basis of the conducted research, the authors proposed a design of a hydrodynamic cavitation apparatus, where each subsequent cavitator along the flow has a smaller size than the previous one. In this case, the hydrody namic treatment mode should ensure the stage of cavitation behind the last cavitator in the range of 2.5—2.6.
Keywords: кавітація; кавітаційна обробка; емульсії; гідродинамічний кавітаційний апарат; cavitation; cavitation treatment; emulsions; hydrodynamic cavitation apparatus; кафедра машин і апаратів харчових та фармацевтичних виробництв; кафедра експертизи харчових продуктів